The Dajjal in Islamic Prophetic Tradition: Between Literalism and Symbolic Interpretation - Zaini, Muhammad (Prodi Ilmu Hadis Fakultas Ushuluddin dan Filsafat UIN Ar-Raniry Banda Aceh, 2025)
The figure of the Dajjāl has long stood as a compelling yet contested subject within Islamic eschatology. While numerous ḥadīths describe his characteristics and role in the end times, scholars remain divided over whether the Dajjāl should be understood as a literal being or as a symbolic representation of deception and corruption. This study examines a selection of Prophetic traditions concerning the Dajjāl, focusing on their textual meaning and contextual interpretation within Islamic thought. Drawing upon the six canonical collections of ḥadīth (Kutub al-Sittah), the analysis explores both the literal attributes attributed to the Dajjāl—such as his one eye and false claims to divinity—and broader readings that link him to ideological, civilizational, or moral threats in history. The study finds that while classical scholars tended toward literal interpretations, modern Muslim thinkers often adopt a symbolic approach, framing the Dajjāl as a reflection of systemic injustice and spiritual misguidance. Ultimately, the article argues that the Dajjāl tradition, whether interpreted literally or metaphorically, serves as an enduring ethical warning about the dangers of falsehood, the fragility of faith, and the importance of moral discernment in times of trial.